Carbon Microbelt Aerogel Prepared by Waste Paper: An Efficient and Recyclable Sorbent for Oils and Organic Solvents. Issue 17 (10th February 2014) - Bi, Hengchang; Huang, Xiao; Wu, Xing; Cao, Xiehong; Tan, Chaoliang; Yin, Zongyou; Lu, Xuehong; Sun, Litao; Zhang, Hua
<x xml:space="preserve">Abstract</x> A carbon microbelt (CMB) aerogel with good selective sorption can be produced in large scale by using waste paper as a precursor. The CMB aerogel shows highly efficient sorption of organic liquids (pump oil: up to 188 times its own weight; chloroform: up to 151 times its own weight). Moreover, the CMB aerogel can be regenerated many times without decrease of sorption capacity by distillation, or squeezing depending on the type of pollutants. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>